Proteome Analysis of Outer Membrane Vesicles From a Highly Virulent Strain of Haemophilus parasuis - Zhang, Kunli; Chu, Pinpin; Song, Shuai; Yang, Dongxia; Bian, Zhibiao; Li, Yan; Gou, Hongchao; Jiang, Zhiyong; Cai, Rujian; Li, Chunling (Frontiers in Veterinary Science, 2021)
Haemophilus parasuis has emerged as an important bacterial pathogen in pig husbandry, as H. parasuis can coinfect pigs with a variety of pathogenic microorganisms and further cause an aggravation of the disease. It is crucial to investigate its pathogenetic mechanism. Gram-negative bacteria naturally secrete outer membrane vesicles (OMVs), and their potent virulence factors play prominent roles that affect the interaction between bacteria and host. Still, the pathogenesis that is associated with the bacterial OMVs has not been well-elucidated. In this study, we investigated the secretion of OMVs from a clinical H. parasuis isolate strain (H45). In addition, we further analyzed the characterization, the comprehensive proteome, and the virulence potential of OMVs. Our data demonstrated that H. parasuis could secrete OMVs into the extracellular milieu during infection. Using liquid chromatography with tandem mass spectrometry (MS/MS) identification and bio-information analysis, we identified 588 different proteins associated with OMVs. Also, we also analyzed the subcellular location and biological function of those proteins. These proteins are mainly involved in immune and iron metabolism. Moreover, we confirmed the pathogenicity of H. parasuis OMVs by observing a strong inflammatory response in J774A.1 and porcine alveolar macrophages. Taken together, our findings suggested that OMVs from H. parasuis were involved in the pathogenesis of this bacterium during infection.